2015
DOI: 10.1021/acs.molpharmaceut.5b00032
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of Drug Biocrystals: A Role for Counterion Transport Pathways in Intracellular Drug Disposition

Abstract: In mammals, highly lipophilic small molecule chemical agents can accumulate as inclusions within resident tissue macrophages. In this context, we characterized the biodistribution, chemical composition and structure of crystal-like drug inclusions (CLDIs) formed by clofazimine (CFZ), a weakly basic lipophilic drug. With prolonged oral dosing, CFZ exhibited a significant partitioning with respect to serum and fat due to massive bioaccumulation and crystallization in the liver and spleen. The NMR, Raman and Powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 44 publications
7
62
0
Order By: Relevance
“…Our results demonstrated that CLDIs are comprised of subdomains of pure CFZ-hydrochloride crystals [34], bounded by multilamellar membrane structure of biological origin [18,19]. Consistent with these previous results, quantitative polarization microscopy revealed the manner in which microscopic domains of ordered CFZ molecules within CLDIs of live macrophages obtained from CFZ-treated mice differentially interact with polarized light.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results demonstrated that CLDIs are comprised of subdomains of pure CFZ-hydrochloride crystals [34], bounded by multilamellar membrane structure of biological origin [18,19]. Consistent with these previous results, quantitative polarization microscopy revealed the manner in which microscopic domains of ordered CFZ molecules within CLDIs of live macrophages obtained from CFZ-treated mice differentially interact with polarized light.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, we have characterized the molecular organization and chemical composition of CLDIs following biochemical isolation, using nuclear magnetic resonance, powder X-ray diffraction, transmitted electron microscopy, freeze fracture electron microscopy, liquid chromatography and mass spectrometry [18,19,34]. Our results demonstrated that CLDIs are comprised of subdomains of pure CFZ-hydrochloride crystals [34], bounded by multilamellar membrane structure of biological origin [18,19].…”
Section: Discussionmentioning
confidence: 75%
“…Many of these microorganisms tend to infect and reside within macrophages. Interestingly, chemical analysis of CFZ biocrystals has revealed that they are composed of protonated hydrochloride salt of CFZ (CFZ-HCl) within membrane-bound intracellular compartments (9). Therefore, the bioaccumulation of CFZ biocrystals in macrophages could serve to maximize the therapeutic efficacy of CFZ without significant side effects.…”
Section: Figmentioning
confidence: 99%
“…In previous studies, it has been shown that following prolonged oral administration of CFZ, the drug massively bioaccumulates as intracellular biocrystals in resident tissue macrophages (8)(9)(10)(11)(12). Therefore, it is natural to assume that this bioaccumulation phenomenon contributes to the drug's toxicity, whereas the soluble form of CFZ, which circulates and partitions to and from the different organs, is responsible for CFZ's mechanism of action.…”
mentioning
confidence: 99%
“…Clofazimine (CFZ) is a model xenobiotic - a weakly basic, FDA approved drug for the treatment of leprosy (1) that accumulates in macrophages, forming crystal-like-drug-inclusions (CLDIs) (27). Following biochemical isolation it is possible to analyze the composition of CLDIs, and we have elucidated that CLDIs are comprised of domains of pure CFZ hydrochloride crystals (CFZ-HCl), bound and separated by membranes likely of cellular origin (8). …”
Section: Introductionmentioning
confidence: 99%